ESP-based Approach for Chinese teaching to Foster overseas Students’ Motivation in China - Elmeruche Poumba; Jian Gong (English Department - University of Sultan Ageng Tirtayasa, 2023)
This paper looks into university overseas students’ motivation and needs analysis in the Chinese language teaching-learning process. Its uniqueness lies in exploring English for Specific Purposes (ESP) based approach implications as much effective teaching model able to help teachers foster the motivation of adult learners in Chinese universities. This research was conducted at the university of Science and Technology in a southern province in China. Data were obtained from ten classroom observations and a questionnaire survey during the fall semester. Master’s foreign students attending Chinese class as a compulsory course are the participants of this research. The results have proved that those international students’ motivation and interests are academically and professionally utilitarian. Thereby, the wide gap between the Chinese language teaching methods at the investigated university and the multifaceted needs of students is remarkable. As a matter of fact, such students expect teachers’ support and specific curriculum implication to help them improve language input and output abilities related to their main fields of study for future academic and professional purposes. To continuously maintain overseas students’ motivation toward Chinese and self-study in Chinese universities, our findings strongly suggest using the ESP-based approach as an affordable model for implementing Chinese teaching content specifically in small classroom sessions twice a week. Using the ESP-based approach in small classroom sessions twice a week is a specific and actionable recommendation.